Urban Regeneration in the Brazilian urban policy agenda - Martins, Maria Lucia Refinetti; Santos Pereira, Alvaro Luis dos (European planning studies, 2019)
This article aims to highlight the main arguments that sought to justify the incorporation and legitimization of Urban Regeneration in the urban policy agenda in Brazil. It shows how the convergence between different and even conflicting propositions related to urban development provided ideological support to the construction of discourses in which urban regeneration is portrayed as beneficial to society as a whole, and how recent international ideas on urban development were incorporated in urban policies of contemporary Brazil, considering our local socio-economic and political environment, planning tradition and regulatory frameworks. The focus will be on Rio de Janeiro and particularly São Paulo given the key role these two cities play in defining urban policy paradigms, guiding government agendas and exporting regulatory models to other parts of Brazil.